Evaluasi Paradigma Pengelola Aset dalam Pengelolaan Barang Milik Daerah (BMD): Studi pada Pemerintah Daerah Istimewa Yogyakarta (DIY) - Agus Warsito (Jurnal Bina Praja, 2025)
The government is actively campaigning for the asset manager paradigm as a new approach to realizing more effective and efficient asset management. However, until now, local governments are still struggling to evaluate the success of the asset manager paradigm due to the lack of adequate measurement instruments. This research aims to evaluate the success of the asset manager paradigm in managing Regional Property (BMD). Evaluation of the success of the manager asset paradigm can be carried out using the asset manager paradigm success index model, which is a composite index of success indicators in activity dimensions that require an asset manager paradigm perspective. These activities include planning needs and budget, use, utilization, as well as security and maintenance. The data used in this research is secondary data in the form of Financial Reports from the DIY Regional Government. This data is used to measure the success of the asset manager paradigm with relevant indicators and formulas. The evaluation results showed a decrease in the average value of the three-dimensional indicators measured and an increase in one other dimensional indicator. The evaluation results also showed that there was still room for Regional Apparatus Organizations (OPD) within the DIY Regional Government to increase the spirit of the asset manager paradigm in BMD management. This research produces a measurement model that can be used by local governments to evaluate the success of the asset manager paradigm in managing BMD. This measurement model can be a reference in developing a more comprehensive asset manager paradigm success measurement model in the future.